The evolution of market structure when there is a sequence of innovations - Vickers, J (Wiley, 1986)
The paper explores the question of how market structure evolves when there is a sequence of opportunities to innovate. Does one firm extend its technological superiority to become increasingly dominant, or does technological leadership constantly change hands in a process of "action- reaction"? A simple duopoly model is proposed, in which the answer to this question depends upon the nature of product market behaviour. In that model, highly competitive product market behaviour leads to increasing dominance, whereas Cournot behaviour may lead to action-reaction.